Multimodal monitoring: practical recommendations (dos and don'ts) in challenging situations and uncertainty - Sharma, Rohan; Tsikvadze, Mariam; Peel, Jeffrey; Howard, Levi; Kapoor, Nidhi; Freeman, William D. (Frontiers in Neurology, 2023)
With the advancements in modern medicine, new methods are being developed to monitor patients in the intensive care unit. Different modalities evaluate different aspects of the patient's physiology and clinical status. The complexity of these modalities often restricts their use to the realm of clinical research, thereby limiting their use in the real world. Understanding their salient features and their limitations can aid physicians in interpreting the concomitant information provided by multiple modalities to make informed decisions that may affect clinical care and outcomes. Here, we present a review of the commonly used methods in the neurological intensive care unit with practical recommendations for their use.